(untitled) (Proceedings OPTIMAL, 2025)
MAdolescence is a time of rapid changes in physical, emotional, mental, hormonal, psychological and social growth. This condition is called puberty, one of the signs of puberty in adolescent girls is menstruation. The first menstruation experienced by a woman is called menarche. During menstruation, the problems experienced by almost all women are discomfort to severe pain, this is often referred to as menstrual pain (dysmenorrhea). Dysmenorrhea is lower abdominal pain, the pain is felt like cramps and can spread to the thighs or lower spine. The type of research used is quasi-experimental with one group pre-test post-test. The subjects in this study were all adolescent girls aged 16-19 years totaling 30 respondents with the Accidental Sampling sampling technique. The statistical test used is the Wilcoxon Signed Ranks test. The results of this study indicate that there is an effect of Sanyinjiao Point Acupressure Therapy on Reducing the Intensity of Dysmenorrhea Pain in Adolescent Girls aged 16-19 years, p-value 0.000.